IMPACT OF INTEGRATED WEED MANAGEMENT ON FLAT-SOWN COTTON (GOS SYPIUM HIRSUTUM L.) - H. Ali; S. A. Abid; S. Ahmad; N. Sarwar; M. Arooj; A. Mahmood; A. N. Shahzad (Journal of Animal and Plant Sciences, 2013)
Field experiments were conducted during 2006 and 2007 to develop an effective integrated method of weed control for conventional flat-sown cotton. Treatments included combinations of chemical (No chemical, Pendimethalin @2.5 L ha-1 , and Glyphosate @4.7 L ha-1) and mechanical (No inter-culturing, Inter-culturing, Hand-weeding, and Inter-culturing + Hand-weeding) methods of weed control. A RCBD experiment with split plot arrangements was laid out; where chemical treatments were kept in main plots while mechanical treatments in subplots. Pendimethlin in combination with different mechanical treatments produced the maximum weed control (97%) at 30 DAS (days after sowing), while at 60 DAS the maximum weed control (91%) was achieved by application of Glyphosate in combination with Inter-culturing + hand-weeding. Highest seed cotton yields 2578 and 3613 kg ha-1 were recorded with application of Pendimethalin in combination with Inter-culturing + hand-weeding, followed by 2468 and 3396 kg ha-1 with application of Pendimethalin in combination with Hand-weeding during 2006 and 2007, respectively. Application of Pendimethalin in combination with Inter-culturing and hand-weeding produced the maximum plant dry weight (kg ha-1). Variations in characteristics of fiber quality i.e. %GOT, staple length (mm), and micronaire (µg inch-1) in response to different treatment combinations were either non significant or significant with very little practical importance. It is suggested that pre-emergence application of Pendimethalin in combination with Inter-culturing + hand-weeding may be used for efficient weed control and higher yields in flat-sown cotton.
Keywords: Weed control; cotton; herbicide; flat sowing; hand-weeding; inter-culturing; integrated weed management